Paying attention to foreign affairs : how public opinion affects presidential decision making - Knecht, Thomas, 1971- (Pennsylvania State University Press, 2010)
"Examines the relationship between public opinion and U.S. foreign policy. Argues that policy making under intense public scrutiny differs from policy making when no one is looking"--Provided by publisher